Effects of the NPL on the banks’ profitability during the pandemic COVID-19: the case of the Republic of Serbia - Nebojša Malenković (Anali Ekonomskog fakulteta u Subotici, 2023)
During the pandemic caused by the new SARS-COV2 virus, the country's economic performance is lower than before the health crisis. The global health crisis has directly and indirectly affected the economic and financial indicators of almost all countries. Regardless of state financial aid, which inevitably prevented the collapse of the national economy and financial markets, certain economic sectors are still facing the consequences of the crisis. One of the reasons for the lower financial performance of countries in this period is the insufficient readiness of banks to deal with non-performing loans. This study aims to consider the profitability of the banking sector in relation to non-performing loans in the Republic of Serbia during the pandemic, using the methods of description, deduction, and regression. In addition, a comparison method was used to assess the ability of banks to deal with non-performing loans during the previous global financial crisis. For statistical data processing, the official data of the National Bank of Serbia was extracted from the statistical section, as well as annual and periodic reports were used.